Comparison of the Recombinant Glucosephosphate Isomerase from Different Zymodemes of Entamoeba histolytica with Their Natural Counterparts by Isoenzyme Electrophoresis - E Razmjou; M Rezaian; A Haghighi; B Kazemi; B Farzami; S Kobayashi; T Nozaki (Tehran University of Medical Sciences, 2005)
Entamoeba histolytica is the etiological agent of invasive amoebiasis, the third leading parasitic cause of mortality in the world. Our aim was to find a molecular correlation between a glucosephosphate isomerase zymodeme analyses in E. histolytica zymodemes. It was demonstrated that natural and recombinant glucosephosphate isomerase enzymes of E. histolytica comigrated in the starch gel electrophoresis, indicating that the isoenzyme pattern of E. histolytica glucosephosphate isomerase could be explained from the primary sequences alone and means that expression of the polypeptides of the described sequences in Escherichia coli are able to reproduce the classical glucosephosphate isomerase isoenzyme patterns.